Interstitial lung diseases: course report - Kreuter, Michael; Wells, Athol; Mehta, Deval R.; Kovchun, Anna (Breathe, 2019)
Tweetable abstract ERSpublications - click to tweetParticipants attending the recent @EuroRespSoc course on interstitial lung diseases share their experiences http://bit.ly/31roKoG